Performance Evaluation of LPG-Fueled Rotary Dryer with Forced Convection for Paddy Post-Harvest Processing - Ida Bagus Alit; I Made Mara (G-Tech: Jurnal Teknologi Terapan, 2026)
Traditional post-harvest draying is often weather-dependent and produces low quality rice, so efficient mechanical technologies are needed for small scale farmers. This study evaluated the performance of an innovative, liquefied petroleum gas (LPG)-fueled rotary dryer engineered for post-harvest paddy processing for small-scale farmers. The system employed an indirect heating mechanism combined with forced convection at an airflow velocity of 2 m/s. Experimental trials were conducted across three drying temperatures: 45°C, 55°C, and 65°C. The results demonstrated that the LPG heating system provided high thermal stability and achieved a robust equilibrium within 30 to 40 minutes. Elevating the operating temperature significantly accelerated moisture diffusion, reducing the drying duration from 180 minutes at 45°C to 120 minutes at 65°C. Although the 65°C treatment achieved the highest initial energy efficiency, it induced severe hygroscopic stresses that dropped the head rice yield (HRY) to 60.7%. Conversely, the 55°C treatment emerged as the optimal operating condition, successfully balancing drying kinetics with grain physical integrity by yielding the highest HRY of 70.2% within 150 minutes. Further research is needed to integrate automatic temperature control systems, as well as an analysis of the economic feasibility of using LPG on a farmer scale.